Estudo de cinzas volantes de uma termelétrica da região metropolitana de Fortaleza-CE para aplicação em camadas granulares de pavimentos - Barros, Kelvia Silva (2015)
This dissertation aimed to evaluate the possibility of reusing fly ash coming from a thermoelectric in the Metropolitan Region of Fortaleza, Brazil, for application in pavement unbound layers. Physical, mechanical, and environmental characterization tests were performed in a local soil, in the ash (classified as a non-inert material), as well in graded stabilized mixtures (soil+ash) and chemically stabilized mixtures (soil+ash+lime). With the results of mechanical tests obtained for the graded stabilized mixtures (soil material, 3 mixtures with 30%, 50%, and 70% of ash, and pure ash), two mixtures were also stabilized with 5% of hydrated lime. These mixtures were evaluated at different curing times (0, 7, 14, and 28 days) by means of California Bearing Ratio (CBR) test, Resilient Modulus (RM), Unconfined Compression Strength (UCS) and Indirect Tensile Strength (ITS). The mixture with the most appropriate characteristics (95% of ashes+5% of hydrated lime) was chosen in order to be compared with a base layer of an asphalt pavement structure on the Brazilian highway BR-222, in a monitored experimental road section. By means of numerical analyses using the CAP3D software, these two structures were compared regarding the deflections occurring on the pavement surface, the horizontal strain at the bottom of the asphalt layer, and the vertical stresses on the top of the subgrade. The results obtained with the experimental program, which was developed for the specific region and soil materials studied in this research, encourage the use of fly ashes in pavement unbound layers.